Effect of Forced Sexual Intercourse on Associations Between Early Sexual Debut and Other Health Risk Behaviors Among US High School Students1. (June 2017) - Lowry, Richard; Robin, Leah; Kann, Laura
ABSTRACT: BACKGROUND: Previous research on associations between early sexual debut and other health risk behaviors has not examined the effect of forced sexual intercourse on those associations. METHODS: We analyzed data from a nationally representative sample of 19, 240 high school students in the United States, age ≥16 years, to describe the effect of forced sexual intercourse on associations between early sexual debut and other health risk behaviors using adjusted prevalence ratios (APR). RESULTS: Early sexual debut and forced sexual intercourse were simultaneously and independently associated with sexual risk‐taking, violence‐related behaviors, and substance use. For example, even after controlling for forced sexual intercourse and race/ethnicity, students who experienced their first sexual intercourse before age 13 years were more likely than students who initiated sexual intercourse at age ≥16 years to have had ≥4 sexual partners during their lifetime (girls, APR = 4.55; boys, APR = 5.82) and to have not used a condom at last sexual intercourse (girls, APR = 1.74; boys, APR = 1.47). CONCLUSIONS: Associations between early sexual debut and other health risk behaviors occur independently of forced sexual intercourse. School‐based sexual health education programs might appropriately include strategies that encourage delay of initiation of sexual intercourse, and coordinate with violence and substance use prevention programs.